The effect of client communication behaviors on agency perceived relationship quality : A case study in Vietnamese advertising sector - Nguyen, Giang (My University, 2019)
Global advertising expenditure has seen a steady year-on-year growth for the past decade. Companies are now focusing on making strategic marketing plan while outsourcing the execution part to professional advertising service companies, also known as advertising agencies. Agency-client relationship has proven to be strategic partnership with financial and reputational meanings to both agency and its client. Such important relationship should be fostered with constant care and nurturing. However, there has been a stretching tear between clients and advertising agencies due to poor communication efforts from both sides in recent years. In relationship marketing literature, there has been studies showing the link between communication and relationship quality. Communication is indeed very important and has impacts on some relationship quality sub-constructs. Nonetheless, literature lacks the holistic research on the construct level of how one affects the other. The focus of most research also is on client part, not on agencies. Therefore, this study aims to evaluate the impact of communication behaviors from client on the perception of relationship quality in agency staff. In order to do that, this study was conducted in Vietnamese advertising sector. This study adopted quantitative explanatory approach that was further carried out using survey method. Within a month of data collection, 104 responses were collected from agency staff in the two biggest cities in Vietnam, Hanoi and Ho Chi Minh City. The results show that there were positive correlations between three out of four communication facets and three relationship quality dimensions. Thus, in advertising sector in a developing economy as Vietnam, there are certain communication behaviors from client that trigger positive perception of relationship quality in agency staff, namely, more reciprocal feedbacks and indirect message content. Frequency and informality of communication did not have prediction power over agency overall perceived relationship quality.
Keywords: Relationship quality, communication, relationship marketing, agency-client relationship